2017
DOI: 10.1016/j.nano.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced brain endothelial activation leads to uptake of electrostatically stabilized iron oxide nanoparticles via sulfated glycosaminoglycans

Abstract: Based on our previous data on the presence of very small superparamagnetic iron oxide nanoparticles (VSOP) on brain endothelial structures during experimental autoimmune encephalomyelitis (EAE), we investigated the mechanisms of VSOP binding on inflamed brain endothelial cells in vivo and in vitro. After intravenous application, VSOP were detected in brain endothelial cells of EAE animals at peak disease and prior to clinical onset. In vitro, inflammatory stimuli increased VSOP uptake by brain endothelial bEnd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Previous studies have shown that Gd-enhancing lesions are present before disease signs become apparent ( Wuerfel et al, 2007 ) but rarely correlate with the presence of characteristic immune infiltrate-derived lesions, a hallmark of EAE and MS ( Nessler et al, 2007 ; Nathoo et al, 2014 ). In contrast, we show that Eu-VSOPs also accumulate in areas that are not enhanced by GBCA and are present at sites of immune cell infiltration, which is in alignment with the literature ( Tysiak et al, 2009 ; Millward et al, 2019 ; Berndt et al, 2017 ). More precisely, we found Eu-VSOPs to be dispersed and mostly located in the vicinity of vessels and ventricles, as indicated in the incidence maps.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that Gd-enhancing lesions are present before disease signs become apparent ( Wuerfel et al, 2007 ) but rarely correlate with the presence of characteristic immune infiltrate-derived lesions, a hallmark of EAE and MS ( Nessler et al, 2007 ; Nathoo et al, 2014 ). In contrast, we show that Eu-VSOPs also accumulate in areas that are not enhanced by GBCA and are present at sites of immune cell infiltration, which is in alignment with the literature ( Tysiak et al, 2009 ; Millward et al, 2019 ; Berndt et al, 2017 ). More precisely, we found Eu-VSOPs to be dispersed and mostly located in the vicinity of vessels and ventricles, as indicated in the incidence maps.…”
Section: Discussionsupporting
confidence: 92%
“…Eu-VSOPs were imaged 24 h after injection when they have been shown to be cleared from the blood ( Wuerfel et al, 2007 ). Therefore, we propose that hypointense signals seen in T2 ∗ images originate primarily from VSOP bound to altered ECM components ( Berndt et al, 2017 ) or from particles phagocytosed by peripheral macrophages or/and activated microglia present at sites of inflammation ( Tysiak et al, 2009 ; Millward et al, 2013 , 2019 ). However, it cannot be excluded that these hypointense signals originate from particles phagocytosed by intravascular immune cells patrolling the endothelium and ready to cross upon inflammatory signals as reported in Masthoff et al, 2018 ( Masthoff et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cells exhibited a dose dependent response with regard to fluorescence property. These results agree with the study of M. Abdollah et al[38] and D. Berndt et al[39] who found that cellular uptake of iron oxide increases in a dose-dependent manner. Cell morphology was not altered in any of the fSPIONs concentration used in the present study.…”
supporting
confidence: 93%
“…Electron microscopy is the gold standard for definitive confirmation of intracellular localization of nanoparticle labels, and is the method of choice. [7][8][9] With its high resolution, electron microscopy can clearly visualize the intracellular compartments with high definition, and visualization of the nanoparticles with this method provides the best assurance of successful cell labeling. Confocal microscopy is commonly used to assess uptake of fluorescently-labeled nanoparticles, and while this is a useful tool most researchers often omit the necessary additional staining steps to detail the plasma membrane, intracellular compartments and cytoskeleton.…”
mentioning
confidence: 99%